Chronic electrical stimulation with a peripheral suprachoroidal retinal implant: a preclinical safety study of neuroprotective stimulation - Abbott, Carla J.; Allen, Penelope J.; Williams, Chris E.; Williams, Richard A.; Epp, Stephanie B.; Burns, Owen; Thomas, Ross; Harrison, Mark; Thien, Patrick C.; Saunders, Alexia; McGowan, Ceara; Sloan, Caitlin; et al. (Frontiers in Cell and Developmental Biology, 2024)
Purpose: Extraocular electrical stimulation is known to provide neuroprotection for retinal cells in retinal and optic nerve diseases. Currently, the treatment approach requires patients to set up extraocular electrodes and stimulate potentially weekly due to the lack of an implantable stimulation device. Hence, a minimally-invasive implant was developed to provide chronic electrical stimulation to the retina, potentially improving patient compliance for long-term use. The aim of the present study was to determine the surgical and stimulation safety of this novel device designed for neuroprotective stimulation.Methods: Eight normally sighted adult feline subjects were monocularly implanted in the suprachoroidal space in the peripheral retina for 9-39 weeks. Charge balanced, biphasic, current pulses (100 µA, 500 µs pulse width and 50 pulses/s) were delivered continuously to platinum electrodes for 3-34 weeks. Electrode impedances were measured hourly. Retinal structure and function were assessed at 1-, 2-, 4-, 6-and 8-months using electroretinography, optical coherence tomography and fundus photography. Retina and fibrotic thickness were measured from histological sections. Randomized, blinded histopathological assessments of stimulated and non-stimulated retina were performed. Results: All subjects tolerated the surgical and stimulation procedure with no evidence of discomfort or unexpected adverse outcomes. The device position was stable after a post-surgery settling period. Median electrode impedance remained within a consistent range (5-10 kΩ) over time. There was no change in retinal thickness or function relative to baseline and fellow eyes. Fibrotic capsule thickness was equivalent between stimulated and non-stimulated tissue and helps to hold the device in place. There was no scarring, insertion trauma, necrosis, retinal damage or fibroblastic response in any retinal samples from implanted eyes, whilst 19 % had a minimal histiocytic response, 19 % had minimal to mild acute inflammation and 28 % had minimal to mild chronic inflammation.Conclusions: Chronic suprathreshold electrical stimulation of the retina using a minimally invasive device evoked a mild tissue response and no adverse clinical findings. Peripheral suprachoroidal electrical stimulation with an implanted device could potentially be an alternative approach to transcorneal electrical stimulation for delivering neuroprotective stimulation.